(untitled) (American Journal of Islam and Society, 2006)
Uzbek president Islam Karimov has gotten away relatively easily with his brutal suppression of the Andijon uprising (May 13-14, 2005), in which the state security forces opened fire on protesters and killed about 700 of them. Despite the fact that this book was written before this event, Shahram Akbarzadeh’s Uzbekistan and the United States: Authoritarianism, Islamism & Washington’s Security Agenda articulates quite well how Karimov came to the point where he could find the courage to become increasingly authoritarian despite Uzbekistan’s bad record of human rights abuses and failed democratic reforms. The author argues that Karimov’s already existing authoritarianism has intensified and yet has been relatively ignored as a result of his close cooperation with the United States in the American-led “war-on-terror.” He argues that the common threat of Islamist extremism has brought the United States and Uzbekistan together and has become a pretext for the latter to continue its repressive policies, which have caused Uzbekistan’s human rights and democratization records to falter even further. Akbarzadeh takes the reader through a series of sociopolitical transformations by which Karimov has sought to consolidate his power. These include the domestic restructuring of the Uzbek political system in the post- Soviet era; regional alignments and power struggles, most notably against Russia; and, finally, Tashkent’s long-sought bilateral relations with the United States, which gained a whole new dimension after 9/11 and throughout the American-led “war on terror.” The author concludes that the cooperation between Tashkent and Washington in the fight against Islamist extremism and, consequently, the latter’s downplaying its concerns about democratic reforms in Uzbekistan, would only encourage Karimov to be more repressive and less accountable toward the citizens of Uzbekistan. The book contributes to the understanding of political developments in the newly independent states by probing the interaction between Uzbek domestic politics and the international political and security agendas ...